Perhitungan Geometri Jalan Dan Daya Dukung Tanah Pada Tambang Batubara di PT. Dasrat Sarana Arang Sejati, Parambahan, Desa Batu Tanjung, Kecamatan Talawi, Kota Sawahlunto. - Khairanisa Ariya; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2023)
Abstract. Haul roads are a facility of crucial importance in mining activities, connecting various location points throughout mining, processing, and sales operations. Optimal and efficient planning is necessary to meet the need for haul roads. Road planning is undertaken to acquire the road geometry required. This includes the bearing capacity of the soil, which is crucial in determining the weight of vehicles that the road can sustain. Therefore, the essential data that is required for the planning process includes the conveyance specifications and the findings from the Dynamic Cone Penetrometer (DCP) test. Based on the executed plan, it was determined that the minimum width required for the haul road is 8.75 m, and 15.14 m at the bend. In addition, the plan's superelevation value is 0.04 (equivalent to 4%), a cross slope of 18 cm, a safety berm of 0.5 m, a bottom width of 1.5 m, and the minimum stopping distance is 19.61 m. Technical term abbreviations are explained upon first use. For the design of pavement thickness on the base layer that has been calculated using the DCP test, it is noted that CBR values not compliant with established standards necessitate backfilling if the result is ≤ 5% and compaction if the result is ≥ 12%, ensuring the planned road meets required standards.